PENGEMBANGAN MINAT BELAJAR DALAM PEMBELAJARAN - P., Andi Achru (Idaarah: Jurnal Manajemen Pendidikan, 2019)
Interest in learning is a driving force from within individuals to conduct learning activities to increase knowledge and skills and experience. This interest grows because of the desire to know and understand something that encourages and directs students’ interest in learning so that they are sincere in their learning. Interest in learning is the tendency of students to conduct learning activities that are driven by a desire to achieve the best possible learning outcomes. Based on the definitions from the experts it can be concluded that the interest in learning is the energy that drives a person to achieve learning goals. Interest in learning does not only depend on ability, but also depends on whether someone chooses mastery goals (learning objectives), the focus of which is to learn a new ability well; or performance goals, the focus of which is to demonstrate or show our abilities to others.